2020
DOI: 10.1021/acsomega.9b03848
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Combination Generator: a Tool for Generating Peptide Combinations

Abstract: Peptides are used as reagents both for basic research and diagnostic purposes. Therefore, there is a need for novel methods for the design of peptide molecules with a particular specific physiochemical profile. The properties of the peptides are governed by the nature of amino acids constituting the peptide. There is a lack of a web server or tools which could predict all the possible combinations of the peptides generated because of the combinations of amino acids based on the physiochemical properties. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Since the factoradic (with 8 components) of 2021 is (0, 1, 2, 0, 4, 4, 2, 0), the permutation (of size 8) of rank 2021 is (0, 3,6,7,1,5,4,2). To obtain this permutation, we read the factoradic from right to left, and extract iteratively from the list (0, 1, .…”
Section: Link Between the Factorial Number System And Permutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the factoradic (with 8 components) of 2021 is (0, 1, 2, 0, 4, 4, 2, 0), the permutation (of size 8) of rank 2021 is (0, 3,6,7,1,5,4,2). To obtain this permutation, we read the factoradic from right to left, and extract iteratively from the list (0, 1, .…”
Section: Link Between the Factorial Number System And Permutationsmentioning
confidence: 99%
“…It is also used as a basic building block in scheduling problems [3], as well as, e.g., in software testing [4]. In other contexts, it appears as the core problem for the generation of complex structures: we can for example cite phylogenetics [5] and bioinformatics [6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the role of leucine and phenylalanine residues has been the subject of other studies involving therapeutic applications of peptides [53][54][55]. In line with this, Sahoo et al (2017) demonstrated that the substitution of leucine for phenylalanine significantly increases the toxic effect of cathelicidin-5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) against cancer and bacterial cells [56]. Studies have also demonstrated the interaction of these amino acid residues with biomembranes, which is strongly dependent on the specific membrane components [54,57].…”
Section: Discussionmentioning
confidence: 94%
“…In the last years, more than 7% of Food and Drug Administration-approved drugs are peptide-based entities [2]. Yet, the design and refinement of these active structures are highly challenging [3], and several prediction models and tools are being proposed and have been made available in recent years [4,5]. However, despite these bioinformatics and statistical advances, the isolation of peptides from natural sources, the identification by genomic and transcriptomic investigations, or the synthesis of molecular region mimics of target proteins remain useful both to discover new structures and to understand functional aspects that are crucial for the selection of more potent and selective molecules [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…PepCoGen is also a free web server for generating peptides with a specific physicochemical profile [ 48 ]. In particular, the server generates all possible combinations of peptides by modifying the amino acids having a comparable physicochemical property profile at a given position.…”
Section: Open Resources To Expand and Describe The Chemical Spacementioning
confidence: 99%